Radiative feedback in Helmholtz resonators with more than one opening - Dosch, Hans Günter (The journal of the Acoustical Society of America, 2016)
The resonance frequency of a Helmholtz resonator with several openings is derived, taking into account the radiation feedback between the different holes. This is done under the assumption that the distance between the openings is large as compared to their linear dimensions. The effect of a finite wall thickness of the resonator is also discussed. The radiation feedback can lead to a shift of the resonance position by more than 10%.
Gesehen am 25.09.2017